2005
DOI: 10.1051/forest:2005074
|View full text |Cite
|
Sign up to set email alerts
|

Early vegetation dynamics of Pinus tropicalis Morelet forests after experimental fire (W Cuba)

Abstract: -For the first time, fire effects on Pinus tropicalis Morelet (an endemic tree of Cuba) forest is studied. In January 2002, an experimental fire was carried out on a mature Pinus tropicalis forest in the Guaniguanico Mountain Range (W Cuba). Three permanent plots were set and vegetation composition and structure was studied before and one year after fire. The ecological parameters considered were: floristic richness, diversity, abundance, life forms and reproductive strategies of the vegetation. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Vegetation response to fire can vary widely, depending on the burning season [3,36]. In particular, in Mediterranean ecosystems, resprouting ability after summer wildland fires could be lower than after prescribed burning because: (i) prescribed burning generally reaches lower intensities than wildland fires [2,3,16] and (ii) summer water stress can reduce resprouting vigour [1]. However, it is worth mentioning that for those species which in this study have shown intermediate resprouting values, such as I. aquifolium and J. oxycedrus, those individuals which did not resprout did not suffer greater burning intensities than those which had resprouted.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation response to fire can vary widely, depending on the burning season [3,36]. In particular, in Mediterranean ecosystems, resprouting ability after summer wildland fires could be lower than after prescribed burning because: (i) prescribed burning generally reaches lower intensities than wildland fires [2,3,16] and (ii) summer water stress can reduce resprouting vigour [1]. However, it is worth mentioning that for those species which in this study have shown intermediate resprouting values, such as I. aquifolium and J. oxycedrus, those individuals which did not resprout did not suffer greater burning intensities than those which had resprouted.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the present paper focuses on the changes in soil nutrient availability with time since a single episodic fire, where fires are not so frequent. Fire frequency is one of the main factors conditioning the effect of fire on vegetation and soil dynamics (De las Heras et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Se distribuye en Pinar del Río y en la Isla de la Juventud, en las cimas de los cerros y montañas, principalmente en áreas con alta recurrencia de incendios (Samek et al, 1969;De las Heras et al, 2005). Esta especie está adaptada a los fuegos, los árboles adultos dejan caer sus acículas, lo que produce una gran cantidad de material combustible en el suelo, ello promueve la rápida extensión de los incendios (Bisse, 1988).…”
unclassified
“…Esta especie está adaptada a los fuegos, los árboles adultos dejan caer sus acículas, lo que produce una gran cantidad de material combustible en el suelo, ello promueve la rápida extensión de los incendios (Bisse, 1988). El fuego afecta la estructura de la vegetación, la composición fl orística y las caracterís-ticas del suelo de los bosques de P. tropicalis (De las Heras et al, 2005).…”
unclassified